Disequilibrium textures in the Centre Hill complex, Munro Township, Ontario. - Thériault, Robert. (University of Ottawa (Canada), 1992)
The Centre Hill complex is part of the mafic to ultramafic Munro Lake sill that occurs within the Stoughton-Roquemaure Group of the Abitibi Subprovince. The complex is approximately 450 m thick and consists of alternating layers of peridotite and clinopyroxenite overlain by 250 m of gabbroic rocks. Two distinct occurrences of cyclic layering are observed: (1) cyclic units of peridotite and clinopyroxenite in the bottom half of the intrusion; and (2) cyclic units of branching-textured gabbro (BTG) and clotted-textured gabbro (CTG) characteristic of the upper layer of gabbro. The upper part of the gabbro is characterized by the presence of spectacular branching crystals that extend away from the upper contact. The primary composition of the branches is interpreted to have been that of Fe-rich olivine based on the actual secondary assemblage. From petrological observations and geochemical data, it is suggested that the branching olivine crystals grew within a crystal-liquid mush in the later stages of fractionation. Two models based on their appearance within the petrogenetic sequence are proposed: (1) the branching olivine crystals grew from the residual melt of the last batch of magma only; or (2) the branching olivine crystallized in the later stages of each cyclic event. The branching textures are truly fractal objects as they are self-similar over a large range of scale. They consistently yield fractal dimensions approximating 1.6. The branching morphologies were qualitatively and quantitatively simulated on the computer using a variation of the Witten-Sander diffusion limited aggregation (DLA) algorithm. From the simulations, it is established that the growth of branching crystals was limited by diffusion of molecules to the crystal-liquid interface, and that the resulting morphology was controlled by two opposing phenomena: (1) the random aggregation of growth molecules along the crystal periphery without relocation; and (2) the systematic arrangement of molecules onto the growing interface according to the internal crystal structure of the mineral. (Abstract shortened by UMI.)
Keywords: Geology.